Pharmacological Properties of TRIVITAMIKS and INTROVIT Preparations Given to Calves - Egamberganovich, Rejepbayev Joshqin (American Journal of Biomedicine and Pharmacy, 2024)
TRIVITAMIKS is a complex vitamin preparation containing vitamins A (retinol palmitate or retinol acetate), D3 (cholecalciferol) and E (α-tocopherol acetate) in a physiologically justified ratio, which has a synergistic effect on the animal's body, normalizing metabolism, increasing resistance to infectious diseases, improving fertility and stimulating the growth of young animals.